Essential work of fracture and acoustic emission study on TPNR composites reinforced by Kenaf Fiber - Anuar, Hazleen (SAGE Publications, Inc, 2007)
Kenaf fiber (KF) based thermoplastic natural rubber (TPNR) composite was produced by melt blending with polypropylene (PP). Kenaf fiber (15% by volume) and TPNR were mixed in as Haake 600p internal mixer. The fracture behavior of the TPNR matrix and of TPNR–kenaf (with and without maleic anhydride grafted polypropylene, MAPP) composites was evaluated using the essential work of fracture (EWF) method and double edge notched tensile (DENT) specimens. Various ligament lengths were employed ranging from 4 to 12 mm. The strain rate was fixed at 2 mm/min. The specific work of fracture (we) and plastic work (bwp) showed the highest energy for TPNR that corresponds to its ductility and allows the application of the EWF approach. It was found that the presence of kenaf fibers and MAPP reduced the toughness of TPNR and changed the ductile fracture to brittle behavior. SEM observation revealed that energy absorption mechanisms include matrix deformation, fiber pullout, and fiber breakage. Acoustic emission (AE) was employed to analyze the failure processes further. The signals emitted by composites were substantially higher than that of the TPNR matrix, reflecting that also the failure mechanisms were affected by the fibers incorporated.